Sport Expertise: The Role of Precise Timing of Verbal-Analytical Engagement and the Ability to Detect Visual Cues. (April 2014) - Taliep, Mogammad Sharhidd; John, Lester
This study proposed that relative timing of high-alpha (10–12 Hz) left (T3) and right (T4) cortical temporal electroencephalographic (EEG) power levels would differentiate performance groups in a reactive sport such as cricket batting. The time course of EEG event-related alpha synchronisation (ERS) and desynchronisation was investigated in two groups (eight skilled and ten less skilled) of right-handed cricket batsmen whilst viewing projected video footage of a bowler delivering a randomised series of 24 deliveries repeated 10 times (total of 240 deliveries). Ball release from the bowler's hand was used as the corresponding reaction cue. Participants were instructed to press one of two buttons on a keypad to identify in-swingers or out-swingers. T3 ERS was significantly greater in skilled batsmen from approximately 1500 ms prior to ball release, but differences reduced close to ball release, reaching nonsignificance by 250 ms. There was no significant difference in T4 between the groups. This study uniquely highlights that the relative timing of the T3 high-alpha ERS state appears to differentiate batting skill groups in a reactive task.